Hypothermia post-cardiopulmonary resuscitation with low inputs: an experience report - Maria Thereza Bugalho Lazzarini; José Carlos Bonjorno Junior; Márcio Pimentel Fernandes; Ana Lúcia Gargione Galvão de Sant´Anna; Regimar Carla Machado
ABSTRACT Objective: to report the experience of conducting directed temperature control of a post-cardiopulmonary resuscitation patient, with reduced and basic inputs available at the institution. Method: an experience report of directed temperature control in patient (age 15 years), after four hours of cardiopulmonary resuscitation in an Intensive Care Unit of a hospital in São Paulo State countryside in 2016, according to the protocol suggested by the American Heart Association, in 2015. There were applications of cold compresses, plastic bags with crushed ice and rectal temperature control. Results: after eight hours, temperature had reached 93.2 ºF. Body cooling was maintained for 24 hours. However, bags with crushed ice were used in the first 6 hours. Conclusion: conduct of nurses to obtain the body cooling with reduced and basic inputs was effective during the stay at the Intensive Care Unit.